LINKED AUDIO REPRESENTATION IN CYBERCARTOGRAPHY: GUIDANCE FROM ANIMATED AND INTERACTIVE CARTOGRAPHY FOR USING SOUND - Brauen, Glenn; Taylor, D. R. Fraser (Revista Brasileira de Cartografia, 2009)
This paper discusses sound representation in cybercartographic atlas projects and products as one example of the application of multisensory representation in contemporary cartography. Auditory representation, like animated and interactive visual cartography, makes explicit use of the temporal dimension. Educational multimedia studies have argued that effective learning outcomes result from the coordinated interpretation of visual and auditory information and from the cognitive relations that learners develop within and between their mental representations of these materials. Based on this previous work, this paper examines the goals and motivations of research into animated and interactive cartography to determine which of those could or have been applied to the use of sound as a media for linked abstract representation in which meaning is conveyed both by the content carried by each sensory mode as well as by the manner of relations between visual and auditory representations, signified by the coordinated reactions of the visual and auditory components of atlas products to user actions. To illustrate key concepts in this discussion, the paper describes an application prototype that allows a user to examine data concerning Canada's trade with world regions using an audio-visual interface. The paper outlines a set of functional roles that this type of linked auditory representation could fulfill within an audio-visual cartography, drawing on functional analyses of interactive and animated cartography and acoustic analogies developed through the analysis of the motivations and goals of dynamic visual cartography.